2009
DOI: 10.1089/scd.2008.0215
|View full text |Cite
|
Sign up to set email alerts
|

Human GPM6A Is Associated With Differentiation and Neuronal Migration of Neurons Derived from Human Embryonic Stem Cells

Abstract: Glycoprotein M6A (GPM6A) is known as a transmembrane protein and an abundant cell surface protein on neurons in the central nervous system (CNS). However, the function of GPM6A in the differentiation of neurons derived from human embryonic stem (ES) cells is unknown. To investigate the function of GPM6A in neural differentiation, we generated human ES cell lines with overexpressed (B2h-oeM6A) or suppressed (B2h-shM6A) human GPM6A. Real-time polymerase chain reaction (PCR) showed that overexpression of GPM6A ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 32 publications
1
39
1
Order By: Relevance
“…Remarkably, the myelin proteolipid protein (PLP/DM20) family members, such as GPM6A, GPM6B, and PLP1 transcript variant DM20, but not PLP1 (Fernandez et al, 2010), have been shown to be involved in the processes of neurite outgrowth and filopodium formation (Lagenaur et al, 1992; Mukobata et al, 2002; Alfonso et al, 2005; Michibata et al, 2008; Zhao et al, 2008; Fuchsova et al, 2009; Brocco et al, 2010; Scorticati et al, 2011). GPM6A, in particular, is also required for filopodium motility and synaptogenesis (Fuchsova et al, 2009; Brocco et al, 2010), and it has been implicated in neuronal differentiation of human stem cells (Michibata et al, 2009) and PC12 cells (Mukobata et al, 2002). When siRNA methodology is used, GPM6A low-expressing neurons display decreased filopodia numbers and a lower density of synaptophysin clusters (Alfonso et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, the myelin proteolipid protein (PLP/DM20) family members, such as GPM6A, GPM6B, and PLP1 transcript variant DM20, but not PLP1 (Fernandez et al, 2010), have been shown to be involved in the processes of neurite outgrowth and filopodium formation (Lagenaur et al, 1992; Mukobata et al, 2002; Alfonso et al, 2005; Michibata et al, 2008; Zhao et al, 2008; Fuchsova et al, 2009; Brocco et al, 2010; Scorticati et al, 2011). GPM6A, in particular, is also required for filopodium motility and synaptogenesis (Fuchsova et al, 2009; Brocco et al, 2010), and it has been implicated in neuronal differentiation of human stem cells (Michibata et al, 2009) and PC12 cells (Mukobata et al, 2002). When siRNA methodology is used, GPM6A low-expressing neurons display decreased filopodia numbers and a lower density of synaptophysin clusters (Alfonso et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the polygenic nature of neural disorders, the fact that GPM6A is able to cause claustrophobia disorder highlights its importance. The GPM6A encodes the glycoprotein M6A that associated with the differentiation and neuronal migration of neurons derived from undifferentiated human stem cells [39]. Association of the GPM6A with the subgroup of schizophrenia patients reinforces the key role of this gene in regulation of central nervous system (CNS) [8].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, other neuronal surface molecules besides L1 have been shown to promote neuronal differentiation in vitro, which further supports the hypothesis that an overexpression of neuronal cell adhesion molecules in ES cells is a suitable approach towards their application in vivo. ES cells overexpressing the glycoprotein M6A, which is a cell adhesion molecule expressed on neurons in the CNS, differentiated more efficiently into neurons when compared to non-modified control ES cells (Michibata et al, 2009) and the L1-binding partner molecule NCAM significantly increased neuronal differentiation of embryonic neural precursor cells into mature neurons in vitro when added into medium of cultured cells (Shin et al, 2002). However, in contrast to L1, the beneficial effects of ES cells overexpressing these molecules have not been tested in animal models of disease to date.…”
Section: The Effects Of L1 On Neuroectodermal Differentiation Of Es Cmentioning
confidence: 99%